Evaluasi Pelaksanaan Kangaroo Mother Care (KMC) pada Kasus Ibu yang Memiliki Bayi dengan Berat Lahir Rendah - Khulasoh, Khulasoh; Kartini, Farida; Ratnaningsih, Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to evaluate the implementation of Kangaroo Mother Care (KMC) in cases of mothers who have low birth weight (LBW) babies at PKU Muhammadiyah Hospital Yogyakarta. The research method used is qualitative with a case study design. The research results showed that the implementation of KMC at PKU Muhammadiyah Hospital Yogyakarta had followed the established SOP and received a positive response from mothers. The benefits felt include increased emotional bonding between mother and baby, stable baby body temperature, and calm baby. However, mothers face difficulties in implementing KMC at home, especially in installing a sling and depending on the help of others. Additional support is needed to overcome these challenges. In conclusion, KMC has significant benefits in improving the health and development of babies and strengthening the bond between mother and baby. Keywords: BBLR, Evaluation, KCM